Production Planning and scheduling in the Footwear Industry - Moreira, Carlos André Vaz (2022)
In recent years, the Portuguese footwear industry has changed drastically. What used to be a low-cost mass production industry has changed to adapt to the needs of retail chains dealing with small orders and personalized footwear. These changes increase the demand for flexible and fast production lines, able to deliver orders of any size. This thesis deals with production planning for the injection line of a company producing safety shoes. In this study, a new method for the lot-sizing is proposed to balance the production over the following weeks, minimizing the production costs, stocks and backlog requirements. This is complemented with a short-term planning (sequencing) algorithm for dealing with operational requirements. In order to solve these problems, a hierarchical method is used to exchange data between the midterm lot-sizing problem and the scheduling a heuristic, providing feasible solutions to both. Results obtained show that the company can significantly benefit from this new planning method.